(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The goal was to analyze the effects of aerobic training on a range of cardio respiratory endurance and muscular endurance variables among female athletes aged 18–24, who had been training for at least two years. In order to conduct this study, twenty four female athletes were picked at random from Punalur, Kollam district, Kerala, India. Age varied among the subjects chosen; they spanned between 15 to 17 years. With 12 participants per group, the sample consisted of Group ’I’, receiving Aerobic training, and Group ’II’, serving as the control group. Group ’I’ engaged in a training plan spanning three days, including one session every twenty-four hours. Sessions typically extended from sixty to ninety minutes. No specific training was received by members of control group (Group ’II’). Cardio respiratory endurance and muscular endurance were measured using the Cooper 9-minute walk/run test and wall sit test. Pre and post-test data collection focused on predetermined variable criteria before and following the training session. Statistical methods were applied to examine the pre and post-tests scores via dependent -’t’ tests and ANCOVA respectively. Examining the results, it became clear that the aerobic training program had a substantial effect on improving cardio respiratory endurance and muscular endurance within the experimental population. Control group members demonstrated neither notable advancements nor statistically meaningful differences across three key performance indicators (cardio respiratory endurance and muscular endurance).